Enzymatic butanolysis of coconut oil. Biorefinery approach. (1st December 2017) - Bouaid, Abderrahim; Acherki, Hassan; García, Alicia; Martinez, Mercedes; Aracil, Jose
Highlights: The transesterification of a low cost and sustainable coconut oil, using enzymatic catalysis with butanol as alcohol to realize a completely green bio-process. The biorefinery approach has been used to evaluate the integrated process of coconut oil to produce a more valuable LMWBE fraction and a clean biodiesel process from HMWBE to overcome the economic problem. The different variables affecting the enzymatic butanolysis of coconut oil have been studied and optimized. Biobutanol was used as alcohol also in order to meet the challenging requirement of low temperature properties of the esters. Abstract: The biorefinery approach, consisting in the transesterification of a low cost and sustainable coconut oil, using enzymatic catalysis with butanol as alcohol to realize a completely green bio-process. The proposed biorefinery approach uses an integrated process for the production of two fractions, the first one LMWBE (low molecular weight) caprylate, caprate, laurate and myristate butyl esters which can be used as high values chemicals (due to their numerous applications in cosmetic, pharmaceutical, and food industries), the second remaining fraction HMWBE (high molecular weight) palmitate, stearate and oleate butyl esters could be used as a promising substitute for conventional fuels, since it matches the European Biodiesel Standard EN 14214. The influence of variables such as temperature, catalyst concentration and alcohol/oil molar ratio on the production of both fractions has been studied and optimized by means of factorial design and response surface methodology (RSM). The obtained models are useful to determine the optimum operating conditions for an up-scaled industrial process, using a minimum number of experiments, with the consequent benefits from an economical point of view. However from a technical point of view, the highest possible yield for the more valuable LMWBE fraction should be targeted, consequently a catalyst concentration of 5.8% an alcohol/oil molar ratio of 6.2:1 and an operation temperature of 65 °C should be chosen. According to these conditions, conversion rates of 74% and 24% for LMWBE and HMWBE, respectively, could be obtained. The preparation of the products is a green engineering process, clean, solvent-free, with a very selective catalyst that minimizes water and energy consumption and the downstream processing of the integrated process.